Can We Improve Confusion, Uremia, Respiratory Rate, Blood Pressure, Age >65 with Lactate and Procalcitonin to Predict Mortality in Pneumonia? - Ahmet Burak Urfalioglu; Satuk Bugra Yapici; Durdu Mehmet Uzucek; Dervis Yildiz; Kemal Sener; Adem Kaya; Akkan Avci; Sadiye Yolcu (Dubai Medical Journal)
Introduction: Pneumonia is a common diagnosis in the emergency department (ED). Some scoring systems such as Confusion, Uremia, Respiratory Rate, Blood Pressure, Age>65 (CURB-65) are used to determine the severity of this disease. We aimed to determine the best scoring system (CURB-65, serum lactate+CURB-65, serum procalcinonin+CURB-65) to predict the severity and 30-day mortality of pneumonia patients admitted to our ED. Methods: This study was planned as a prospective study. 480 community-acquired pneumonia patients admitted to our ED between February 1, 2020, and January 31, 2021, were included. CURB-65 score, CURB-65+lactate levels, and CURB65+procalcitonin levels were evaluated to predict disease severity. Results: A total of 480 pneumonia patients, 281 (58.5%) men and 199 (41.5%) women, with a mean age of 61.7 ± 19.06 years, were included in the study. The sensitivity/specificity pair and cut-off value of CURB-65 for 30-day mortality was 71.9/74.8%. These values were 68.5% and 61.9% for CURB-65+lactate (cut-off = 17.50) and 78.1% and 90.7% for CURB-65+procalcitonin (cut-off = 2.095). Discussion: Infectious diseases such as pneumonia, urinary tract infection, and sepsis are common reasons for ED presentations and may be fatal, especially in the elderly population. In such infectious diseases, it is difficult to predict the prognosis of the patients including discharge, hospitalization service, mortality probability in the EDs those are becoming much more crowded each day and several scoring systems have been improved. In this study, the highest sensitivity and specificity were determined in CURB-65+procalcitonin. Conclusion: CURB-65 is superior to CURB-65+lactate; however, CURB-65+procalcitonin is superior to both in predicting 30-day mortality.